Hubungan Komunikasi dan Empati Perawat dengan Kepuasan Pasien BPJS Rawat Inap di Rumah Sakit Rajawali Citra Bantul Yogyakarta - Dewi, Susyana Candra Santi (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Backround: The quality of service provided by a hospital significantly influences patient satisfaction. However, many hospitals provide poor service to patients, such as poor communication and a lack of empathy. Several studies have shown that BPJS patients often receive poor service, resulting in lower patient satisfaction. Objective: This study aims to measure the influence of communication and empathy on BPJS patient satisfaction at Rajawali Citra Hospital, Bantul, Yogyakarta. Method: The research design is an analytic survey. By using a cross sectional approach. The samples taken in this study used the formula for the number of samples to estimate the proportion of an unlimited population using accidental sampling. Data were analyzed using chi square test. Result: There is a correlation between communication and patient satisfaction with inpatient BPJS at Rajawali Citra Pleret hospital, Bantul in 2022, namely -Sig = 0.004 <alpha p = 0.05, there is a correlation between empathy and satisfaction with BPJS inpatient care at Rajawali Citra Hospital Pleret Bantul in 2022, namely the value of P-Sig = 0.010 <alpha p = 0.05, and there is a correlation between competence and satisfaction of BPJS inpatient patients at Rajawali Citra Pleret Hospital Bantul in 2022, namely the value of P-Sig = 0.036 <alpha p = 0.05. Conclusion: There is a correlation between empathic, communication and nurse competence with patient satisfaction inpatient BPJS at Rajawali Citra Hospital, Bantul, Yogyakarta in 2022.